A study of DNA methylation in myotonic dystrophy. Issue 3 (March 1993) - Shaw, D J; Chaudhary, S; Rundle, S A; Crow, S; Brook, J D; Harper, P S; Harley, H G
Abstract : We have examined the hypothesis that the severe congenital form of myotonic dystrophy is caused by genomic imprinting at the level of differential DNA methylation of maternal and paternal alleles. Probes encompassing the 5', central, and 3' regions of the myotonic dystrophy protein kinase gene were used on blots of blood DNA from congenital and adult onset patients, digested with combinations of methylation sensitive and insensitive restriction enzymes. We observed similar patterns of methylation in each of the different classes of patient, and found no methylation differences between paternally and maternally derived alleles. Within the limitations of the experiment, our results provide no evidence for a role for genomic imprinting in congenital myotonic dystrophy and suggest that the explanation for this form of the disease will be found elsewhere.